The Role of Civic Education in Building Political Awareness of Generation Z Young People - Sri Yunita; Yeremia Afrianto Manalu; Yuni Naftali Naibaho; Marsella Pascha Sidabutar; Astri Conia Vasya Tarigan (Edumaspul: Jurnal Pendidikan, 2023)
Civic Education has a high role in increasing the spirit of nationality, especially for generation Z as the nation's successor who is expected to contribute to his country.Our reason for choosing the role of civic education in building young people's political awareness and many generation z who prefer abstention in general elections because they think that there are no political parties that can be trusted.This research uses interview and documentation methods. The interview method is like asking generation Z youth about the role of Civic Education in shaping political awareness and the documentation method we do is like taking pictures to document the physical or visual state of an event object.Many young people are less aware of politics in addition to generation Z youth do not care about politics.Starting from questions to high school students who say that civic education lessons do not increase awareness of politics.Then there are also many generation Z youth who do not use their voting rights or choose to abstain, fulfilled with quite logical reasons.Rethinking the importance of political participation in realizing political democracy. It is appropriate for young people to open political insights so that whatever public opinion is given regarding the political process is not accepted raw. Because one vote in the general election will determine the direction this nation will take. Choosing is not easy, but not choosing is not a wise attitude..